2012
DOI: 10.1021/nl300572y
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Terahertz Plasmons and Magnetoplasmons in Large Scale Monolayer Graphene

Abstract: We show that in graphene epitaxially grown on SiC the Drude absorption is transformed into a strong terahertz plasmonic peak due to natural nanoscale inhomogeneities, such as substrate terraces and wrinkles. The excitation of the plasmon modifies dramatically the magneto-optical response and in particular the Faraday rotation. This makes graphene a unique playground for plasmon-controlled magneto-optical phenomena thanks to a cyclotron mass 2 orders of magnitude smaller than in conventional plasmonic materials… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
240
0
17

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(280 citation statements)
references
References 42 publications
23
240
0
17
Order By: Relevance
“…This phenomenon has been demonstrated by Witowski and coauthors, 35 and it was also observed very recently in graphene layers epitaxially grown on SiC. 25,26 To understand this behavior, it is useful to explore the asymptotic behaviors of graphene conductivities in the high doping limit. In highly doped graphene at lower energies, the interband transitions can be ignored and only the E n → E n+1 (E n < μ c < E n+1 ) intraband transition dominates in Eqs.…”
Section: Edge Magnetoplasmons In Graphene Disksmentioning
confidence: 57%
See 1 more Smart Citation
“…This phenomenon has been demonstrated by Witowski and coauthors, 35 and it was also observed very recently in graphene layers epitaxially grown on SiC. 25,26 To understand this behavior, it is useful to explore the asymptotic behaviors of graphene conductivities in the high doping limit. In highly doped graphene at lower energies, the interband transitions can be ignored and only the E n → E n+1 (E n < μ c < E n+1 ) intraband transition dominates in Eqs.…”
Section: Edge Magnetoplasmons In Graphene Disksmentioning
confidence: 57%
“…Graphene magnetoplasmons have been studied theoretically in infinite graphene sheets, [19][20][21][22] semi-infinite sheets, 23,24 and finite structures. 25,26 As a linear and gapless energy spectrum, graphene has a different Landau level (LL) distribution compared with a usual 2DES, reading…”
Section: Magneto-optical Conductivities Of Graphenementioning
confidence: 99%
“…The sample is measured in the 0.5-2.5 THz frequency range using time-domain spectroscopy. The complex conductivity of the graphene stack is then retrieved using a dedicated formulation 8,35,36 . Details regarding the fabrication, measurement and stack conductivity extraction process are provided in Methods.…”
Section: Resultsmentioning
confidence: 99%
“…During the preparation of this manuscript, we became aware of a related work 31 presented by Crassee et al at APS March Meeting. In that work, magneto-plasmons were observed in unpatterned epitaxial graphene on SiC due to the inherent domain boundaries.…”
Section: Main Textmentioning
confidence: 99%